Crisis Prevention: Tackling Horizontal Inequalities. - Stewart, F (Oxford Department of International Development, 2000)
This paper analyses the economic and social causes of conflict, drawing conclusions for conflict prevention. Civil wars normally occur when groups mobilize against each other, on the basis of some cultural characteristic like ethnicity or religion. It is suggested that horizontal inequalities, i.e. inequalities among groups in political, economic and social dimensions, provide the basis for inter group animosity. Policies to limit excessive horizontal inequalities are needed in all vulnerable countries.